解方程 2x^2-4x+1=0 x^2-5x-6=0
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 07:15:29
解方程2x^2-4x+1=0x^2-5x-6=0解方程2x^2-4x+1=0x^2-5x-6=0解方程2x^2-4x+1=0x^2-5x-6=02x^2-4x+1=0x=(4±√8)/4∴x=(2+√
解方程 2x^2-4x+1=0 x^2-5x-6=0
解方程 2x^2-4x+1=0 x^2-5x-6=0
解方程 2x^2-4x+1=0 x^2-5x-6=0
2x^2-4x+1=0
x=(4±√8)/4
∴x=(2+√2)/2 x=(2-√2)/2
x^2-5x-6=0
(x-6)(x+1)=0
∴x=6 x=-1
2x^2-4x+1=0
等式两边同除以2,得
x²-2x=-1/2
两边+1,得
(x-1)²=1/2
解得x=±√2/2-1
x^2-5x-6=0
楼上做对了。
解方程(x/x(x+2))+(x/(x+2)(x+4))+.+x/(x+8)(x+10)=1
解方程:2/x^2+x+3/x^2-x-4/x^2-1=0
解方程:(4/x-2)+(x-1/x-5x+6)+(2/3-x)=0
(x-1)(x-3)(x-4)(x-12)+5x^2=0解方程
解方程2x/x+2-x/x-2-x+11/4-x方=1
解方程:2x(x-2)-6x(x-1)=4x(1-x)+16
解方程x(x-1)(x-2)(x-3)(x-4)=24x=?
解方程 x(2x-4)+3x(x-1)=5x(x-3)+8
解方程(x²-x+4)x-(x-1)(x²+2)=x+7
解方程(x+1/x-1)+(x-2/x+2)+(x-3/x+3)+(x+4/x-4)=4
解方程:(x+3)/(x+2)-(x+4)/(x+3)=(x+5)/(x+4)-(x+2)/(x+1)
解方程 x+2/x+1+x+8/x+7=x+6/x+5+x+4/x+3
解方程:2x+4x+6x...+100x=1-(x+3x+5x+...+99x)
解方程 (x+2)/(x+1) - (x+4)/(x+3)=(x+6)/(x+5)-(x+8)/(x+7)
解方程;x/x-4=5x/x-2
解方程:x(x-4)=(x-2)(x-6)
解方程x/(x-2)=2x/(x-3)+(1-x)/(x-5x+6)
解方程:x(x+2)-4x=0